Study on low-temperature drying characteristics of premodified sludge with calcium oxide and sawdust - ZHANG Qunli; WANG Han; WANG Baozhong; CHENG Xuanrui; ZHANG Qiuyue (Gongye shui chuli)
Heat pump drying is a low-carbon and energy-saving sludge drying method. The operating temperature of heat pump is generally no more than 70 ℃. In order to improve the drying rate of sludge at low-temperature, the effects of air parameters and additives on sludge drying characteristics at low-temperature were studied by experimental research and data analysis methods. Experimental results showed that when the air temperature was 50-70 ℃ and the air velocity was 0.5-1.7 m/s, increasing the air temperature, air velocity and the additive ratio could accelerate the drying process of sludge. The average and maximum drying rates of CaO and sawdust premodified sludge were increased by 14.2% and 25.7%, respectively, compared with pure sludge. Two-way analysis of variance (ANOVA) showed that drying temperature had a greater impact on sludge drying than air velocity. Through non-linear curve fitting, the dynamic model of sludge drying process with temperature and air velocity changes was constructed, which provided a data basis for sludge drying under low-temperature conditions.